PENGARUH KENAIKAN PENGHASILAN TIDAK KENA PAJAK (PTKP) TERHADAP PENINGKATAN DAYA BELI MASYARAKAT DI DAERAH KABUPATEN KEDIRI (Studi Kasus Di Desa Sambireksik Kecamatan Gampengrejo) - Jonathan, Gorby (Jurnal Mahasiswa Perpajakan, 2014)
Developing countries such as Indonesia's state government development is necessary in order to make this country better and grow into a developed country. Income tax article 21, the biggest contributor of government revenue. Itself taxable income is income that is not taxed. Policy PTKP rise in 2013 was taken by the government for fiscal stimulus in anticipation of a global economic slowdown. The purpose of this study is the effect of the increase in taxable income to purchasing power in the region, especially the village of Kediri District Gampengrejo Sambiresik. Researchers wanted to examine the truth by raising the taxable income will increase purchasing power also appropriate government said. This type of research used in this study is a quantitative approach. Data collection techniques used questionnaire study. This study used a Likert scale scores of the questionnaire. Analysis of the data used is descriptive analysis. The results of this research is that if the independent variable (PTKP) worth (0) then the dependent variable (Purchasing Power) worth 3,938. Leverage the value of coefficient for the variable X is equal to -180. In the regression tests are sig 0.140, then H0 is accepted. Advice from research that more closely if the government wants to increase the amount of taxable income to increase purchasing power. The government can increase people's purchasing power by raising the taxable income but also control the prices of basic necessities. Keywords : income taxes , non-taxable income and purchasing power.